Sie sind auf Seite 1von 5

Table of Fourier Transform Pairs

Definition of Inverse Fourier Transform Definition of Fourier Transform

1 jwt - jwt
f (t ) =
2p F (w )e dw F (w ) = f (t )e dt
- -

f (t - t 0 ) F (w )e - jwt0

f (t )e jw 0t F (w - w 0 )

f (at ) 1 w
F( )
a a

F (t ) 2pf (-w )

d n f (t ) ( jw ) n F (w )
dt n

(- jt ) n f (t ) d n F (w)
dw n

t F (w )
+ pF (0)d (w )
f (t )dt
jw
-

d (t ) 1

e jw 0 t 2pd (w - w 0 )

sgn (t) 2
jw

Signals & Systems - Reference Tables 1

1 sgn(w )
j
pt

u (t ) 1
pd (w ) +
jw

Fn e jnw 0t 2p Fnd (w - nw 0 )
n = - n = -

t wt
rect ( ) tSa( )
t 2

B Bt w
Sa( ) rect ( )
2p 2 B

tri (t ) w
Sa 2 ( )
2

pt t Ap cos(wt )
A cos( )rect ( )
2t 2t t (p ) 2 - w 2
2t

cos(w 0 t ) p [d (w - w 0 ) + d (w + w 0 )]

sin(w 0 t ) p
[d (w - w 0 ) - d (w + w 0 )]
j

u (t ) cos(w 0 t ) p
[d (w - w 0 ) + d (w + w 0 )] + 2 jw 2
2 w0 - w

u (t ) sin(w 0 t ) p 2
[d (w - w 0 ) - d (w + w 0 )] + 2w 2
2j w0 - w

u (t )e -at cos(w 0 t ) (a + jw )
w 02 + (a + jw ) 2

Signals & Systems - Reference Tables 2

u (t )e -at sin(w 0 t ) w0
w 02 + (a + jw ) 2

e
-a t 2a
a2 +w2
2
/( 2s 2 ) 2
w2 / 2
e -t s 2p e -s

u (t )e -at 1
a + jw

u (t )te -at 1
(a + jw ) 2

Trigonometric Fourier Series

f (t ) = a 0 + (a n cos(w 0 nt ) + bn sin(w 0 nt ) )
n =1

where

1 T 2T
a0 =
T 0 f (t )dt , a n = f (t ) cos(w 0 nt )dt , and
T0
2T
bn = f (t ) sin(w 0 nt )dt
T 0

Complex Exponential Fourier Series

1T
f (t ) = Fn e jwnt
, where Fn = f (t )e - jw 0 nt dt
T 0
n = -

Signals & Systems - Reference Tables 3

Some Useful Mathematical Relationships

e jx + e - jx
cos( x) =
2

e jx - e - jx
sin( x) =
2j

sin( 2 x) = 2 sin( x) cos( x)

2 cos2 ( x) = 1 + cos(2 x)

2 sin 2 ( x) = 1 - cos(2 x)

cos 2 ( x) + sin 2 ( x) = 1

Signals & Systems - Reference Tables 4

Useful Integrals

sin(x)
cos( x)dx
- cos(x)
sin( x)dx
cos( x) + x sin( x)
x cos( x)dx
sin( x) - x cos( x)
x sin( x)dx

x
2
cos( x)dx 2 x cos( x) + ( x 2 - 2) sin( x)

x
2
sin( x)dx 2 x sin( x) - ( x 2 - 2) cos( x)

ax
e dx e ax
a

ax
xe dx x 1
e ax - 2
a a

2 ax
x e dx x 2 2x 2
e ax - 2 - 3
a a a

dx 1
a + bx b
ln a + bx

dx 1 bx
a 2 + b 2x2 tan -1 ( )
ab a